Determinación y Análisis de Fórmulas Estructurales de Esmectitas del Estado de Guanajuato - Gallaga Ortega, Yolanda G.; Aguilar Becerra, Salvador; Ramos Ramírez, Esthela (Acta Universitaria, 2002)
In this this article structural formulas of clay minerals are determined from clays coming from the geologic localizations at Comonfort, Jerécuaro, Victoria and San Francisco del Rincón, in the state of Guanajuato, México. After applying, the Moore and Reynold’s method of chemical composition, it was deduced dioctahedral or trioctahedral type, layer charge origin and value, and the specific clay mineral from the analysis of the resulting formula. Two montmorillonites type minerals, a beidellite type and a vermiculite type mineral were obtained, and the last one showed a trend to be a part of the esmectite-vermiculite series.
Keywords: Array; Array; Array; Array; Array; Array